2018
DOI: 10.1091/mbc.e17-06-0362
|View full text |Cite
|
Sign up to set email alerts
|

Translational control of a human CDKN1A mRNA splice variant regulates the fate of UVB-irradiated human keratinocytes

Abstract: Phosphorylation of eIF2 and the integrated stress response in response to UVB are cytoprotective by a mechanism featuring preferential translation of a specific splice variant of CDKN1A that facilitates G1 arrest and subsequent DNA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 66 publications
(96 reference statements)
1
17
0
Order By: Relevance
“…It remains unexplored the possibility that the different transcript variants are preferentially associated with one or other cell fate. Additionally, translational regulation at the 5’ UTR of the variants has been shown to affect cell fate [ 11 , 21 ]. Human cells also express several Cdkn1a transcript variants [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains unexplored the possibility that the different transcript variants are preferentially associated with one or other cell fate. Additionally, translational regulation at the 5’ UTR of the variants has been shown to affect cell fate [ 11 , 21 ]. Human cells also express several Cdkn1a transcript variants [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human cells also express several Cdkn1a transcript variants [ 22 ]. Among the ten human transcript variants currently annotated, at least one (transcript variant 4) shares translational regulatory mechanisms with the murine p21var2 [ 21 ]. Interestingly, even though murine variant 2 and human variant 4 do not appear to share sequence homology, the translational regulation in both transcripts is driven by the integrated stress response and results in cell cycle arrest [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4A , Supplementary Table 1 ). Upregulation of CDKN1A by UVB is tightly controlled by MDM2 and p53 [ 45 , 46 ]. CDKN1A regulates cell cycle progression at G1 by inhibiting cyclin-CDK2 or -CDK4 complexes, regulates DNA repair in S-phase by interacting with proliferating cell nuclear antigen (PCNA), and has p53 independent effects on cell cycle and apoptosis [ 47 ] ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…41 In a recent report, Collier et al indicated that when cells in response to sublethal ultraviolet B radiation, genome-wide analysis reveals preferential translation of a series of genes undergoing AS events following radiation, of which the CDKN1A splice variants regulated the fate of radiation-insulted human keratinocytes. 42 Other environmental stresses, such as hypoxia, have been also found to induce the occurrence of alternative events. As stated in the study reported by Bowler et al, hypoxia leads to significant changes in AS in prostate cancer cells and the CLK splice factor kinase could be targeted in cancers in which hypoxia contributes to cancer therapy resistance.…”
Section: Discussionmentioning
confidence: 99%